Comparison of long‐term drug survival and safety of biologic agents in patients with psoriasis vulgaris. (1st January 2015) - Gniadecki, R.; Bang, B.; Bryld, L.E.; Iversen, L.; Lasthein, S.; Skov, L.
Summary: Background: Drug survival (time to drug discontinuation) has recently emerged as an important parameter reflecting the long‐term therapeutic performance in a real‐life setting. Biologic drug survival in psoriasis is mainly limited by a gradual loss of efficacy over time. Previous studies have been limited by small patient population size and short observation times and yielded discrepant survival times for different biologics. Objectives: To calculate the long‐term drug survival for adalimumab, etanercept, infliximab and ustekinumab in a large cohort of real‐life patients with psoriasis vulgaris and to analyse the factors that influence drug survival. Patients and methods: Data were extracted from the prospective registry DERMBIO covering all patients with psoriasis vulgaris treated with biologic agents in the academic centres in Denmark. Drug survival was analysed using the Kaplan–Meier method. The influence of different covariates on drug survival was analysed by Cox regression. Results: Included in the analysis were 1867 treatment series (adalimumab n = 774, etanercept n = 449, infliximab n = 253, ustekinumab n = 391) administered in 1277 patients for up to 10 years. Drug survival was significantly longer for ustekinumab than for anti‐tumour necrosis factor (TNF)‐α agents ( P < 0·001). Etanercept had the shortest survival time [median survival 30 months, 95% confidence interval (CI) 25·1–34·9] whereas adalimumab and infliximab had comparable survival rates (59 months, 95% CI 45·6–72·4; 44 months, 95% CI 33–54·9, respectively). Survival was longer in men [odds ratio (OR) 1·51, 95% CI 1·31–1·74 vs. women] and in patients who had not previously received any biologic agent (OR 1·24, 95% CI 1·05–1·46). Loss of efficacy accounted for 67% of all drug discontinuations. Conclusions: Ustekinumab has a significantly longer drug survival than the anti‐TNF‐α agents. Switching from one biologic to another is associated with an impairment of drug survival. Preventing loss of efficacy is a major area of medical need in the biologic therapy of psoriasis and the strategies that improve drug survival should be further investigated.